Co-occurring congeners coordinate drought and shade tolerance traits along gradients of canopy openness - Sam W. Anderson; Jackson Cramer; Katherine A. McCulloh (Oecologia, 2026)
Physiological traits related to water status and photosynthesis biophysically link plant performance to environmental conditions like light and water availability. By approaching the concept of species’ niches from a trait-based perspective, physiological traits can be used to characterize how trait syndromes diverge to limit direct resource competition and promote resource partitioning in sympatric species. Such traits could also inform broader studies of changing community composition in an era of drastic shifts in climate or disturbance regimes. However, the extent of inter/intraspecies trait variation and how such traits vary along local environmental gradients remains an open question in understanding physiological traits as species-level characteristics. To address this, we quantified hydraulic and gas exchange traits in four co-occurring Viburnum species while also quantifying local canopy coverage and soil conditions. All species displayed significant variation in gas-exchange traits, turgor loss point, and heavy carbon isotope discrimination along gradients of canopy openness. Specifically, plants in shadier environments exhibited higher photosynthetic rates at low light levels while individuals growing in gaps demonstrated higher drought tolerance and stricter stomatal regulation. Soil texture explained little variation in traits assessed. V. acerifolium displayed a more conservative, shade-tolerant trait syndrome, yet little significant difference was found in traits between the congeners, highlighting the potentially limited resolution of physiological traits to differentiate trait syndromes of closely related, co-occurring species.

Anthropogenic mortality on coral reefs in Caribbean Panama predates coral disease and bleaching - Katie L. Cramer; Jeremy B. C. Jackson; Christopher V. Angioletti; Jill Leonard‐Pingel; Thomas P. Guilderson (Ecology Letters, 2012)
Ecology Letters (2012) Abstract Caribbean reef corals have declined precipitously since the 1980s due to regional episodes of bleaching, disease and algal overgrowth, but the extent of earlier degradation due to localised historical disturbances such as land clearing and overfishing remains unresolved. We analysed coral and molluscan fossil assemblages from reefs near Bocas del Toro, Panama to construct a timeline of ecological change from the 19th century—present. We report large changes before 1960 in coastal lagoons coincident with extensive deforestation, and after 1960 on offshore reefs. Striking changes include the demise of previously dominant staghorn coral Acropora cervicornis and oyster Dendrostrea frons that lives attached to gorgonians and staghorn corals. Reductions in bivalve size and simplification of gastropod trophic structure further implicate increasing environmental stress on reefs. Our paleoecological data strongly support the hypothesis, from extensive qualitative data, that Caribbean reef degradation predates coral bleaching and disease outbreaks linked to anthropogenic climate change.